Risk of antibiotic treatment failure in premenopausal women with uncomplicated urinary tract infection. Issue 10 (13th April 2021) - Butler, Anne M.; Durkin, Michael J.; Keller, Matthew R.; Ma, Yinjiao; Dharnidharka, Vikas R.; Powderly, William G.; Olsen, Margaret A.
Abstract: Purpose: Acute uncomplicated urinary tract infections (UTIs) are among the most common indications for antibiotic prescriptions in otherwise healthy women. We compared the risk of treatment failure of antibiotic regimens for outpatient treatment of UTI in real‐world practice. Methods: We identified non‐pregnant, premenopausal women diagnosed with uncomplicated, lower tract UTI and prescribed an oral antibiotic with activity against common uropathogens. We used propensity score‐weighted Kaplan–Meier functions to estimate 30‐day risks and risk differences (RD) for pyelonephritis and UTI‐related antibiotic prescription switch. Results: Of 1 140 602 patients, the distribution of index prescriptions was 44% fluoroquinolones (non‐first‐line), 28% trimethoprim‐sulfamethoxazole (TMP/SMX) (first‐line), 24% nitrofurantoin (first‐line), 3% narrow‐spectrum β‐lactams (non‐first‐line), 1% broad‐spectrum β‐lactams (non‐first‐line), and 1% amoxicillin/ampicillin (non‐recommended). Compared to the risk of pyelonephritis for nitrofurantoin (0.3%), risks were higher for TMP/SMX (RD, 0.2%; 95% CI, 0.2%–0.2%) and broad‐spectrum β‐lactams (RD, 0.2%; 95% CI, 0.1%–0.4%). Compared to the risk of prescription switch for nitrofurantoin (12.7%), the risk was higher for TMP/SMX (RD 1.6%; 95% CI 1.3%–1.7%) but similar for broad‐spectrum β‐lactams (RD −0.7%; 95% CI −1.4%‐0.1%) and narrow‐spectrum β‐lactams (RD −0.3%; 95% CI −0.8%–0.2%). Subgroup analyses suggest TMP/SMX treatment failure may be due in part to increasing uropathogen resistance over time. Conclusions: The risk of treatment failure differed by antibiotic agent, with higher risk associated with TMP/SMX versus nitrofurantoin, and lower or similar risk associated with broad‐ versus narrow‐spectrum β‐lactams. Given serious safety warnings for fluoroquinolones, these results suggest that nitrofurantoin may be preferable as the first‐line agent for outpatient treatment of uncomplicated UTI.